The Power of Discourse in Postmetaphysics: Between Dialectical Materialism and Transcendentalism - A. S. Merzenina (Социология власти)
The article examines the significance of “postmetaphysics” as a continuation of Derrida’s philosophy of deconstruction for resolving the philosophical conflict between the transcendental and dialectical traditions of thought. The “postmetaphysical” trend seeks to rethink the relationship between language and power, trying to find a way to talk about power in a way that does not theoretically reproduce the power of metaphysical discourse. It also seeks to avoid the mistake of systems that criticize metaphysical discourse, which is that the criticism itself often takes on a sophisticated form of metaphysics, the source of which is hidden as much as possible. The central phenomenon that is deconstructed in Christian postmetaphysical philosophy in the text is “political ontotheology”, that is, the powerful metaphysical discourse used to build a political ideology. At the beginning of the article, the author examines two ways of formulating onto-theology in philosophy — transcendental and dialectical. It is argued that both directions in the modern era are confronted with their own impasse: transcendentalism cannot conceive of theory as a practical realization of thought, dialectics cannot get rid of the formulation of transcendental supra-historical truth in its practice. The text synthesizes the concepts of Caputo, Vattimo, and Desmond in order to propose a political-religious project that continues Derrida’s philosophy. It is concluded that post-metaphysics as a “weak thought” can change and weaken political structures without completely dialectically moving into political onto-theology, but it cannot be a field completely independent of metaphysics or replace it.